Uncoupling of ammonia oxidation from nitrite oxidation: Impact upon nitrous oxide production in non-cropped Oregon soils. (January 2017) - Giguere, Andrew T.; Taylor, Anne E.; Suwa, Yuichi; Myrold, David D.; Bottomley, Peter J.
Abstract: The factors controlling the relative contributions of ammonia- (NH3 ) oxidizing archaea (AOA) and bacteria (AOB) to nitrification and nitrous oxide (N2 O) production in soil remain unclear. A study was conducted to examine the contributions of AOA and AOB to nitrification, nitrite (NO2 − ) accumulation, and NO2 − -affected N2 O production in three non-cropped Oregon soils. Nitrification potential rates in the three soils ranged seven-fold from 0.15 to 1.08 μmol N g −1  d −1, with AOA contributing 64–71% of the total activity. AOA- and AOB-driven NO2 − accumulation represented 8–100% of total NO2 −  + NO3 − accumulation, persisted over 48 h, and was accompanied by acetylene-sensitive, ammonium- (NH4 + ) stimulated N2 O production. Ammonium- and NO2 − -dependent N2 O production occurred when both AOA and AOB, or AOA alone were active. By adding the NO2 − -oxidizing bacteria, Nitrobacter vulgaris, to soil slurries to increase NO2 − -oxidizing capacity, both NO2 − accumulation and N2 O production were prevented, while the overall rate of nitrification was unaffected. Yields of N2 O-N amounted to 0.05 ± 0.01% of total NO2 −  + NO3 − -N accumulation in the presence of supplemental NH4 +, and 0.28 ± 0.11% in the presence of both supplemental NH4 +  + NO2 − . Regression analysis of the N2 O production against NO2 − accumulation over 24 h revealed a positive, non-linear relationship for N2 O production by both AOA plus AOB and by AOA alone. Values of V max ranged 12-fold from 0.05 to 0.62 nmol N2 O g −1 d −1, and predicted K m values for NO2 − ranged 15-fold from 0.02 to 0.30 μmol NO2 −  g −1 soil. These findings provide new insights into the impact of NO2 − accumulation in soils on N2 O production by both AOA and AOB, and show that NO2 − accumulation primarily drives N2 O formation in these soils, and increases N2 O yield by both AOA and AOB. Highlights: Soil AOA- and AOB-driven NO2 − accumulation represented 8-100% of total nitrification. Both AOA- and AOB-driven N2O production were dependent on NO2 − accumulation. Enhancing soil NO2- oxidizing capacity prevents NO2 − accumulation and N2O production. AOA- and AOB-driven N2O yields were influenced by NO2 − concentration. Kinetic parameters were determined for N2O production by AOA and AOB.